Tandem Walking Exercise on Muscle Strength in The Elderly in Prunggahan Kulon Village Semanding District, Tuban - Dinia Laily Oktavia; Dyah Pitaloka; Hyan Oktodia Basuki; Suhartono Suhartono (Asosiasi Dosen Muda Indonesia, 2026)
The decline in muscle strength among older adults is a major health concern that contributes to reduced mobility, increased risk of falls, and decreased quality of life. This issue becomes more critical as the elderly population continues to grow, particularly in community-based settings where simple and accessible interventions are needed. Objective: This study aimed to analyze the effect of tandem walking exercise on muscle strength in older adults in Prunggahan Kulon Village, Semanding District, Tuban. Methods: This study employed a quantitative pre-experimental design using a one-group pre-test and post-test approach. A total of 63 elderly participants were selected through purposive sampling. Data were collected using the 30-Second Chair Stand Test (30s-CST) to measure lower limb muscle strength before and after the intervention. The data were analyzed using the Wilcoxon Signed Rank Test. Results: The findings showed a significant improvement in muscle strength after the intervention, where most participants shifted from moderate to high muscle strength categories. Statistical analysis indicated a significant difference between pre-test and post-test results (p < 0.05). Implications: Tandem walking exercise can be applied as a simple, low-cost, and effective intervention to improve muscle strength and reduce fall risk among older adults, particularly in community-based settings. Originality: This study provides new evidence on the effectiveness of tandem walking exercise as a specific balance-based intervention focusing on muscle strength as the primary outcome in a village-based elderly population, which remains limited in previous studies.